2020
DOI: 10.1155/2020/1985379
|View full text |Cite
|
Sign up to set email alerts
|

Beta Blocker Therapy in Heart Failure Patients with Active Cocaine Use: A Systematic Review

Abstract: Background. Cocaine use is associated with multiple cardiovascular complications including heart failure. The use of different types of beta blockers in heart failure patients with active cocaine use is still a matter of debate. In this review, our objective is to systematically review the available literature regarding the use of beta blockers in the treatment of heart failure patients with concurrent cocaine use. Methods. PubMed, EMBASE, Web of Science, and Clinical Trials.gov were searched from inception to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…For example, stimulant use is a known risk factor for CVD; however, substance use is generally absent from CVD risk assessments and treatment plans. 42 Furthermore, despite evidence that β-blockers are a safe and effective intervention for heart failure among people who use cocaine 43,44 their use in this population is often avoided, due in part to stigma and misinformation. 45 Consistent with prior studies, 11 NFOD events made up approximately 94% of all overdose events in this study and the incidence of NFOD was more than 15 times that of fatal events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, stimulant use is a known risk factor for CVD; however, substance use is generally absent from CVD risk assessments and treatment plans. 42 Furthermore, despite evidence that β-blockers are a safe and effective intervention for heart failure among people who use cocaine 43,44 their use in this population is often avoided, due in part to stigma and misinformation. 45 Consistent with prior studies, 11 NFOD events made up approximately 94% of all overdose events in this study and the incidence of NFOD was more than 15 times that of fatal events.…”
Section: Discussionmentioning
confidence: 99%
“…For example, stimulant use is a known risk factor for CVD; however, substance use is generally absent from CVD risk assessments and treatment plans . Furthermore, despite evidence that β-blockers are a safe and effective intervention for heart failure among people who use cocaine their use in this population is often avoided, due in part to stigma and misinformation …”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review also supports use of β-blockers as a component of guideline-directed medical therapy in patients with cocaine use and comorbid HFrEF, citing improvements in the New York Heart Association functional class, left ventricular ejection fraction, and 30-day readmission rate. 13 Altogether, these studies encourage the continued use of β-blocker therapy in patients with cocaine use, both during hospitalization and on discharge.…”
Section: What We Should Do Instead Of Routinely Holding β-Blockers In...mentioning
confidence: 90%
“…There is some weak evidence in support of the use of beta-blockers among cocaine users with heart disease. In a systematic review (n = 1994 from 12 studies), it was found that beta-blockers conferred either a beneficial or a neutral effect on primary outcomes in heart failure in patients actively using cocaine [ 44 ]. It should be noted that there are no large-scale studies on beta-blockade in active cocaine users and the information from this meta-analysis comes mainly from small, single-center, retrospective studies [ 44 ].…”
Section: Reviewmentioning
confidence: 99%
“…In a systematic review (n = 1994 from 12 studies), it was found that beta-blockers conferred either a beneficial or a neutral effect on primary outcomes in heart failure in patients actively using cocaine [ 44 ]. It should be noted that there are no large-scale studies on beta-blockade in active cocaine users and the information from this meta-analysis comes mainly from small, single-center, retrospective studies [ 44 ]. Furthermore, this study evaluated patients with heart failure, which is not the only clinical cardiovascular manifestation of long-term cocaine use.…”
Section: Reviewmentioning
confidence: 99%